2003
DOI: 10.2139/ssrn.307419
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Possible Proxies of Corporate Bond Liquidity

Abstract: We consider eight different proxies (issued amount, coupon, listed, age, missing prices, yield volatility, number of contributors and yield dispersion) to measure corporate bond liquidity and use a five-variable model to control for interest rate risk, credit risk, maturity, rating and currency differences between bonds. The null hypothesis that liquidity risk is not priced in our data set of euro corporate bonds is rejected for seven out of eight liquidity proxies. We find significant liquidity premia, rangin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
55
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 74 publications
(56 citation statements)
references
References 59 publications
1
55
0
Order By: Relevance
“…For example, Chordia et al (2003), Chacko (2005), Driessen (2005) and Downing et al (2007) showed that liquidity risk is a major determinant of observed credit spreads. 3 Other studies including Collin-Dufresne et al (2001), Delianedis and Geske (2001), Perraudin and Taylor (2003), Houweling et al (2005), Ericsson and Renault (2006) and Van Landschoot (2008), De Jong and Driessen (2012), Chen et al (2014), Tseng et al (2014) and Schwartz (2014), also showed a strong, negative relationship between credit spreads and liquidity. 4 In fact, a decrease in the corporate bond market's liquidity implies a market preference for less risky assets and a higher risk premium to cover the liquidity risk.…”
Section: Theoretical and Empirical Backgroundmentioning
confidence: 94%
See 1 more Smart Citation
“…For example, Chordia et al (2003), Chacko (2005), Driessen (2005) and Downing et al (2007) showed that liquidity risk is a major determinant of observed credit spreads. 3 Other studies including Collin-Dufresne et al (2001), Delianedis and Geske (2001), Perraudin and Taylor (2003), Houweling et al (2005), Ericsson and Renault (2006) and Van Landschoot (2008), De Jong and Driessen (2012), Chen et al (2014), Tseng et al (2014) and Schwartz (2014), also showed a strong, negative relationship between credit spreads and liquidity. 4 In fact, a decrease in the corporate bond market's liquidity implies a market preference for less risky assets and a higher risk premium to cover the liquidity risk.…”
Section: Theoretical and Empirical Backgroundmentioning
confidence: 94%
“…In practice, however, they seem to have limited explanatory power (e.g. Jones et al 1984;Ogden 1987;Delianedis and Geske 2001;Elton et al 2001;Lyden and Saraniti 2000;Houweling et al 2005;Ericsson and Renault 2006), leading to the belief that other common factors exist that explain the remaining variation.…”
Section: Theoretical and Empirical Backgroundmentioning
confidence: 99%
“…Although most of the studies focused on the US markets, a bunch of contributions analysed data on euro-denominated bonds (Annaert and De Ceuster, 1999;McGinty, 2001;Dìaz and Navarro, 2002;Houweling et al, 2005;.…”
Section: The Determinants Of Corporate Bond Liquidity: a Survey Of Thmentioning
confidence: 99%
“…Another rationalization hinges on the low-information-costs argument (large issues have less information costs, since more information is disseminated among investors and more investors own and analyze them). In addition, smaller issues are more easily absorbed by buy-and-hold investors who reduce trading and, hence, liquidity (see Houweling et al, 2005, for references on these views). However, some contrarian evidence is provided by McGinty (2001) who finds that the issued amount has a negative impact on liquidity.…”
Section: The Determinants Of Corporate Bond Liquidity: a Survey Of Thmentioning
confidence: 99%
See 1 more Smart Citation